Answer:
Step-by-step explanation:
Given equation can be re written as
............(i)
Now it is given that y(π/2) = 2e
Applying value in (i) we get
ln(2e) = sin(π/2) + c
=> ln(2) + ln(e) = 1+c
=> ln(2) + 1 = 1 + c
=> c = ln(2)
Thus equation (i) becomes
ln(y) = sin(x) + ln(2)
ln(y) - ln(2) = sin(x)
ln(y/2) = sin(x)
It would be circular since it was cut from a cylindrical log.
Hope This Helps You!
Good Luck Studying :)
(s + 3t) * (2s - 2t) = 2s^2 - 2st + 6ts - 6t^2
Answer:
D
Step-by-step explanation:
IM RLY SORRY IF THIS IS WRONG IM DOING THIS FORM MEMORY
so I'm pretty sure u the arch equals twice the angle
so pi/2*2 = pi so D
hope it helppsss
trying not to dieT-T
Answer:
(3/5)x+1/4=(3/4)x-2/5
<=> (3/5)x - (3/4)x= -2/5 - 1/4
<=> x(12/20 - 15/20) = -13/20
<=> x(-3/20) = -13/20
<=> x = 13/3
Step-by-step explanation: